English language learning strategies employed by Malay part time learners of UiTM in the northern region of Malaysia / Budiman Sabri Ahmad - Ahmad, Budiman Sabri (Universiti Teknologi MARA, Perlis, 2011)
The present research is an investigation into the repertoire of English language learning strategies employed Malay part-time learners learning English as a second language of UiTM in the northern region of Malaysia. The goal of the study is to help the learners improve their English proficiency. The objectives are to find out the level of the learners’ learning strategies employed in learning English; and also to find out which strategies are mostly employed in their learning of English. The participants of the study are 120 Malay part-time learners learning English as a second language in four branches of UiTM in the northern region of Peninsular Malaysia; viz, UiTM Perlis, UiTM Kedah, UiTM Penang, and UiTM Perak. The simple random approach is used in determining the respondents. The instruments used are two structured questionnaires, – adapted Oxford’s (1990) SILL, version 7.0 and respondents’ background information – and semi-structured interview based on Wenden’s (1987) guidelines. The questionnaire data were analyzed using SPSS and the interview data were transcribed and analyzed based on Wenden’s guidelines (1987). Results of the study showed that the Malay part-time learners are at the average level in using strategies learning English. The type of strategies they used seem to be the metacognitive strategies. This seems consistent with some studies done in foreign countries as well as in Malaysia. The researcher concluded that there is a need to train the learners in other types of learning strategies besides the metacognitive strategies, so that the learners could be extend their repertoire of learning strategies which in turn would help them in learning English and thus improve their proficiency of the English language.